1986
DOI: 10.1159/000116023
|View full text |Cite
|
Sign up to set email alerts
|

Isoelectric Focusing and Two-Dimensional Gel Electrophoresis in Plasma and Cerebrospinal Fluid from Patients with Dementia

Abstract: IgG profiles of cerebrospinal fluid (CSF) and plasma from patients with Alzheimer’s disease/senile dementia of Alzheimer type, multi-infarct dementia and aged nondemented individuals were analyzed using isoelectric focusing (IEF) followed by immunofixation and high resolution two-dimensional polyacrylamide gel electrophoresis (PAGE). The IEF profiles of plasma and CSF in patients with dementia were diffuse and lacked oligoclonal bands and were identical to those of nondemented individuals. The investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Also, the number and type of patients studied have varied. In the present study, again, no disease-specific alterations in 2-D protein maps between the dementia and control groups could be observed, which is in agreement with earlier reports (24)(25)(26). Nevertheless, although no definitive markers are available, recent studies suggest that there may be quantitative differences in the amount of certain proteins in the CSF between AD and age-matched control patients (27-3 1).…”
Section: Resultssupporting
confidence: 93%
“…Also, the number and type of patients studied have varied. In the present study, again, no disease-specific alterations in 2-D protein maps between the dementia and control groups could be observed, which is in agreement with earlier reports (24)(25)(26). Nevertheless, although no definitive markers are available, recent studies suggest that there may be quantitative differences in the amount of certain proteins in the CSF between AD and age-matched control patients (27-3 1).…”
Section: Resultssupporting
confidence: 93%
“…Several 2-DE studies have been performed without successful identification of AD-specific changes in the CSF proteome (58)(59)(60)(61). In the early 1990's, we found that an isoform of haptoglobin-alpha)1 chains was present in the majority of 2-D maps in AD vs. age-matched controls, indicating a possible altered blood-brain-barrier function in AD (62).…”
Section: -De Studies In Admentioning
confidence: 84%
“…Although the occurrence of CNS specific OCB in the CSF of patients with Alzheimer's disease was first reported in 1980 [16] this and subsequent reports have only evaluated relatively small numbers of patients [1,5,10] [3,4,7,8]. The presence of OCB in primary neurodegenerative dementia is generally considered to be a rarity such that their absence is supportive of diagnosis, specifically for example of probable AD [13].…”
Section: Introductionmentioning
confidence: 99%